Solid, gel, and liquid carbohydrate format effects on gut comfort and performance - Guillochon, M.; Rowlands, D. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Carbohydrate sports drinks produce worthwhile benefits to endurance performance compared with noncaloric controls. However, athletes now consume carbohydrate in a range of formats, including gels and bars, but the comparable performance outcomes are unknown. Therefore, the aim of this study was to establish the relative effects of drink, gel, bar, and mixed carbohydrate formats on intense cycling performance. In a treatmentapparent randomized crossover design, 12 well-trained male cyclists completed 4 trials comprising a 140-min race simulation, followed by a double-blind slow-ramp to exhaustion (0.333 W·s-1). Carbohydrate comprising fructose and maltodextrin was ingested every 20 min via commercial drink, gel, bar, or mix of all 3, providing 80 g carbohydrate·h-1. Fluid ingestion was 705 ml·h-1. Exertion, fatigue, and gastrointestinal discomfort were measured with VAS. Performance peak power (SD) was 370 (41), 376 (37), 362 (51) and 368 W (54) for drink, gels, bars, and mix respectively. The reduction in power (-3.9%; 90%CI ±4.3) following bar ingestion vs. gel was likely substantial (likelihood harm 81.2%; benefit 0.8%), but no clear differences between drinks, gels, and the mix were evident. Bars also produced small-moderate standardized increases in nausea, stomach fullness, abdominal cramps, and perceived exertion, relative to gels (likelihood harm 95-99.5%; benefit <0.01%) and drink (75-95%; <0.01%); mix also increased nausea relative to gels (95%; <0.01%). Relative to a gel, carbohydrate bar ingestion reduced peak power, gut comfort, and ease of exertion; furthermore, no clear difference relative to drink suggests bars alone are the less favorable exogenous-carbohydrate energy source for intense endurance performance.